Tuberculosis: tendency, prognosis and common risk factors in Santiago de Cuba (2004-2014) - Yanara Toledano Grave de Peralta; Dina Lafargue Mayoz; Mariela Montero Migota; Senia Curí Quevedo; Martha Campos Muñoz (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive, cross-sectional and retrospective study, aimed at describing the historical course of the tuberculosis incidence in Santiago de Cuba, was carried out from 2004 to 2014.  The universe was constituted by 100.0% of the new cases notified by compulsory declaration diseases records. A descending tendency of this disorder was shown, which stayed in the success area; the historical mean in patients aged 25 to 44 prevailed, although in 2014 it decreased in this group.  Important changes were evidenced in the frequency of risk factors, because the closed institution, elderly and alcoholism groups diminished ostensibly; there was only an increase of nicotine addiction. For the next 2 years there was a risk prediction of getting sick of less than 2 cases for every 100 000 inhabitants.